2017
DOI: 10.1136/bmjopen-2017-015906
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation in hip fractures: a systematic review

Abstract: To evaluate the evidence for the resuscitation of patients with hip fracture in the preoperative or perioperative phase of their treatment and its impact on mortality.DesignWe searched MEDLINE, EMBASE, CENTRAL and PROSPERO databases using a systematic search strategy for randomised trials and observational studies investigating the fluid resuscitation of any patient with hip fracture. No language limits were applied to the search, which was complemented by manually screening the reference lists of appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
20
0
2
Order By: Relevance
“…Despite considerable evidence supporting the association between anemia at admission and postoperative morbidity and mortality, a systematic review by Rocos et al 37 found no published prospective studies comparing the utilization of blood products versus fluid resuscitation in preoperative optimization of hip fracture patients. Fluid resuscitation with 1 L of normal saline solution over 8 hours was demonstrated to reduce the hemoglobin level by 7, 11, and 22 g/L for intracapsular, intertrochanteric, and subtrochanteric hip fractures, respectively 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable evidence supporting the association between anemia at admission and postoperative morbidity and mortality, a systematic review by Rocos et al 37 found no published prospective studies comparing the utilization of blood products versus fluid resuscitation in preoperative optimization of hip fracture patients. Fluid resuscitation with 1 L of normal saline solution over 8 hours was demonstrated to reduce the hemoglobin level by 7, 11, and 22 g/L for intracapsular, intertrochanteric, and subtrochanteric hip fractures, respectively 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative chronic conditions and insu cient preoperative optimization in this patient pro le, associated with intraoperative conditions such as intraoperative bleeding and hypovolemia, predispose these elderly patients to hemodynamic instability or arrhythmias during surgery (Alecu et al 2010); (Rocos et al 2017). The occurrence of intraoperative complications may compromise the balance between tissue oxygen delivery and oxygen consumption, and increase the patient's susceptibility to postoperative complications (Merry and Mitchell 2018); (Beecham et al 2020).…”
Section: -Discussionmentioning
confidence: 99%
“…e echo signals received according to the different impedance and attenuation coefficients of the tissue are different. ese signals will be recorded in the ultrasound detector to reflect the changes in the position and intensity of the organs, and then whether the examined organs have lesions is detected [10][11][12]. Ultrasound equipment needs to be combined with an ultrasound imaging system to improve the diagnostic efficiency of the ultrasound department.…”
Section: Introductionmentioning
confidence: 99%